An investigation of data from the first year of the interim Canada Dental Benefit for children <12 years of age - Robert J. Schroth; Robert J. Schroth; Robert J. Schroth; Vivianne Cruz de Jesus; Vivianne Cruz de Jesus; Anil Menon; Anil Menon; Olubukola O. Olatosi; Olubukola O. Olatosi; Victor H. K. Lee; Victor H. K. Lee; Katherine Yerex; et al. (Frontiers in Oral Health, 2024)
IntroductionIn 2022, the federal government announced a commitment of $5.3B to provide dental care for the uninsured, beginning with children <12 years of age. Now referred to as the Interim Canada Dental Benefit (CDB), the program targets those <12 years of age from families with annual incomes <$90,000 without private dental insurance. The purpose of this study was to review federal data from the Government of Canada on public uptake and applications made to the Canada Revenue Agency (CRA) during the first year of the Interim CDB.MethodsData for the first year of the Interim CDB (up to June 30, 2023) were accessed from the Government of Canada Open Data Portal through Open Government Licence—Canada. Rates of children receiving the Interim CDB per 1,000 were calculated by dividing the number of beneficiaries by the total number of children 0–11 years by province or territory, available from Statistics Canada for the year 2021.ResultsDuring the first year of the program, a total of 204,270 applications were approved, which were made by 188,510 unique applicants for 321,000 children <12 years of age. Over $197M was distributed by the CRA. Overall, the national rate for receiving the Interim CDB was 67.8/1,000 children. Ontario (82.5/1,000), Manitoba (77.1/1,000), Nova Scotia (73.4/1,000), and Saskatchewan (72.3%), all had rates of children with the Interim CDB above the national rate.ConclusionsData from the first year of the Interim CDB suggests that this federal funding is increasing access to care for children <12 years by addressing the affordability of dental care. Governments and the oral health professions need to address other dimensions of access to care including accessibility, availability, accommodation, awareness, and acceptability of oral health care.